Transaksi Berjangka Komoditas Pertanian di Desa Sukorejo Perspektif Islam - Fuadi, Septiyan Hudan (Invest Journal of Sharia & Economic Law, 2022)
Nowadays, there are many forms of buying and selling transactions that are developing in the community, one of which is using the futures model on agricultural commodities in Sukorejo Village, Sukorejo District, Ponorogo Regency. The characteristic of this transaction is that the middleman buys agricultural commodities at a higher price than the current market price but the payment is made at a later date. This transaction was motivated by several farmers who found that their harvests were not good due to a lack of personnel in maintaining agricultural products, in addition to unstable price fluctuations due to the COVID-19 pandemic that occurred in Indonesia. Over time, this futures transaction has an impact on the community, namely the harmony of the community is reduced. This research is a field research using descriptive qualitative method. While the purpose of this study is to discuss the validity of the contract and the social impacts that occur from the futures transaction from an Islamic perspective. The conclusion that can be drawn from this research is that futures transactions are valid by contract because in Islam it is also known as Nasi'ah buying and selling. Whereas in the aspect of social impact, in principle, this transaction is worth maslahah because the majority of people feel helped.